Temporal similarity for optical short pulses - Ojeda-Castaneda, Jorge; Gómez-Sarabia, C. M. (Photonics Letters of Poland, 2010)
We define a temporal similarity function for assessing the temporal evolution of short pulses in dispersion media. For first-order dispersion media the temporal similarity function has a simple close expression. We use the sampled values of the temporal similarity function as coefficients, for expressing the output complex amplitude envelope as a finite linear superposition of the input complex amplitude envelope. Full text: PDF References: M. D. Feit and J. A. Fleck, "Calculation of dispersion in graded-index multimode fibers by a propagating-beam method", Appl. Opt. 18, 2843 (1979). [CrossRef] A.W. Lohmann and J. Ojeda-Castaneda, "Fresnel similarity", Opt. Comm. 249, 397 (2005). [CrossRef] A. W. Lohmann, "An array illuminator based on the Talbot-effect," Optik ( Stuttgart) 79, 41-45 (1988). J. R. Leger and G.J. Swanson, "Efficient array illuminator using binary-optics phase plates at fractional-Talbot planes", Opt. Lett. 15, 288 (1990). [CrossRef] V. Arrizón and J. Ojeda-Castaneda, "Multilevel phase gratings for array illuminators", Appl. Opt. 33, 5925 (1994). [CrossRef] J. Ojeda-Castaneda, P. Andrés and O. Mendoza-Yero, "Tailoring temporal intensities at first- and second-dispersion order ", Optical Memory and Neural Networks 18, 260 (2009). [CrossRef] J. P. Guigay, "On Fresnel Diffraction by One-dimensional Periodic Objects, with Application to Structure Determination of Phase Objects", Optica Acta 18, 677 (1971). [CrossRef] M. J. Bastiaans, Signal and Image Representation in Combined Spaces (Academic Press, 1995).